2016
DOI: 10.5606/archrheumatol.2016.5907
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha Gene Polymorphism and Association With Its Serum Level in Iranian Population with Rheumatoid Arthritis

Abstract: Objectives: This study aims to determine whether promoter -238 G/A polymorphism in tumor necrosis factor-alpha (TNF-α) gene is associated with susceptibility to rheumatoid arthritis (RA) in Iranian population and serum level of TNF-a. Patients and methods:This case-controlled study was performed on two groups including 90 RA patients (20 males, 70 females; mean age 50.3 years; range 26 to 65 years) and 90 healthy controls (21 males, 69 females; mean age 48.6 years; range 27 to 63 years). We determined the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…[47] showed no significant difference (p>0.05) in TNF-α protein levels in RA patients between -308 GG and AA or GA genotypes. Similarly, we also concurred with [12] and [48] findings, who demonstrated no relationship between the -308, -238 G/A polymorphism and serum TNF-α levels in Iraqi and Iranian RA patients, respectively. Our findings, on the other hand, contradicted the findings of [49], who discovered that the -308 GA/AA genotype was related with elevated TNF-α levels.…”
Section: Discussionsupporting
confidence: 92%
“…[47] showed no significant difference (p>0.05) in TNF-α protein levels in RA patients between -308 GG and AA or GA genotypes. Similarly, we also concurred with [12] and [48] findings, who demonstrated no relationship between the -308, -238 G/A polymorphism and serum TNF-α levels in Iraqi and Iranian RA patients, respectively. Our findings, on the other hand, contradicted the findings of [49], who discovered that the -308 GA/AA genotype was related with elevated TNF-α levels.…”
Section: Discussionsupporting
confidence: 92%
“…However, this significance disappeared after correction for multiple analysis. Similar to reported findings from Iran on autoimmune or inflammatory diseases, no significant differences were observed in our cohort study in all other SNPs in TNF- α (40–42).…”
Section: Discussionsupporting
confidence: 91%
“…The following points need to be taken into consideration when interpreting our findings. First, previous experimental studies have found that TNF‐α , IL‐1 , or IL‐6 polymorphisms may alter the messenger RNA expression level of TNF‐α, IL‐1, and IL‐6 14,15 . Therefore, these polymorphisms may generate an imbalance status between Th1 and Th2 related immune responses, and ultimately influence the risk of asthma.…”
Section: Discussionmentioning
confidence: 99%